2006
DOI: 10.1080/14756360500424036
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffect of schistosomicidal drugs on hepatic arylsulfatase B from theSchistosoma-infected mouse

Abstract: Arylsulfatase B (ASB) hydrolyzes the desulfation of N-acetylgalactosamine-4-sulfate at the non-reducing terminal of glycosaminoglycans. This enzyme activity was found to be elevated in mice schistosomiasis. In the present study, the catalytic and immunological properties of purified ASB from the liver of Schistosoma-infected mouse was investigated in the presence and absence of the schistosomicidal drugs praziquantel and Commiphora extract. The in vitro effect of praziquantel was found to be inhibitory with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is associated with various degrees of hepatic dysfunction and severe cases of infection can be fatal [10,12]. It has been reported that changes in some enzymes occur during S. mansoni infection and these enzymes belong to different classes of classification [1,2,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with various degrees of hepatic dysfunction and severe cases of infection can be fatal [10,12]. It has been reported that changes in some enzymes occur during S. mansoni infection and these enzymes belong to different classes of classification [1,2,14,17].…”
Section: Introductionmentioning
confidence: 99%